Analisis Penerapan IFRS 16 Pada PT Garuda Indonesia (Persero) Tbk - Filipe Sekar Prasetyani (Jurnal Akuntan Publik, 2023)
The International Accounting Standards Board (IASB), issued International Financial Reporting Standards (IFRS) 16 which treats all leases as finance leases within the lessee company. The lease will be capitalized according to the present value of the lease payments and report the lease asset and liability on the company's balance sheet. With the enactment of IFRS 16, IAS 17 no longer applies. So this research highlights the changes that will occur in financial reports and financial ratios after the enactment of IFRS 16 in the company PT Garuda Indonesia Persero, Tbk which is listed on the Indonesia Stock Exchange (BEI). The method used in this research is the Library Method, namely collecting data and information from books and literature including journals from valid sources to strengthen the theoretical basis and as a basis for reference in writing research and the Document method, namely by collecting data from the object being observed, data is form the 2017 audited financial report. The results obtained from this research are that there was a change in profit of (146,764,604) due to a decrease in operating expenses of 663,142,477 due to the elimination of operating lease expenses. An increase in the number of non-current assets of 6,284,596,468. An increase in the number of long-term liabilities that are due within one year. amounting to 1,386,075,496 Additional long-term finance lease liabilities amounting to 4,751,756,386 Decreased current ratio by 21% There was an increase in Total Debt to Total Asset ratio by 14% There was an increase in Debt to Equity ratio by 525% There was an increase in Net Profit Margin by 3%